Prenuptial Agreement in Manuscript Serat Ambiya Pelemgadung, Sragen, Jawa Tengah - Maulana, Luthfy; Syamsul Arifin; Imam Nawawi; Ahmad Wahyu Sudrajad; Annisa Cahyaningsih (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
This study examines the prenuptial agreement in Serat Ambiya Pelemgadung, Sragen, Central Java, Indonesia. The agreement is a special power considering that some of the existing serat texts are used in photographing husband-wife relationships when they are legal. Therefore, the purpose of this article is to compare the characteristics of Serat Ambiya Pelemgadung with others. In addition, what is the framework and meaning of the prenuptial agreement in Serat Ambiya Pelemgadung. This goal is expected to be achieved by selecting philological, hermeneutical and literature studies methods. There are several things that need to be underlined in this study, in the end, that Serat Ambiya Pelemgadung differs from the content of Serat Ambiya' Pelemgadung produced by Hamengku Buwono V's scriptorium. The philosophical framework and meaning of pre-nuptial agreements are inclined to matrilineal cultural values, such as; a) a commitment to love and provide for his wife, b) provide a business field for his wife, to prepare for the children's old age. the husband, c) bear all the debts of the wife before the marriage, and forbid his wife from debts in the future, and d) the husband promises not to use and demand all of his wife's property.